Studies on the Vegetation of Kumbhalgarh Wildlife Sanctuary in Rajasthan - Pandey, R. P.; Singh, N. P. (Indian Forester, 1999)
The Kumbhalgarh Wildlife Sanctuary lies in Pali and Udaipur Districts of Aravalli hills in Rajasthan. Its area, topography, geology and climate are furnished briefly, however, vegetation is presented in details. The forests are mainly composed of Anogeissus pendula belonging to the Northern Tropical Dry Deciduous Forest Type and are almost similar to the ones of Aravalli hill ranges. Some important plant communities are also indicated.